A comparison of screw versus drill and curettage epiphysiodesis to correct leg-length discrepancy. (1st October 2018) - Troy, M.; Shore, B.; Miller, P.; Mahan, S.; Hedequist, D.; Heyworth, B.; Kasser, J.; Spencer, S.; Glotzbecker, M.
Abstract: Purpose: To compare two common surgical techniques of epiphysiodesis: drill/curettage epiphysiodesis (PDED) versus cross screw epiphysiodesis (PETS). The hypothesis is that the two techniques have similar efficacy but demonstrate differences in length of hospital stay (LOS), time to return to activity and complication rates. Methods: A retrospective review of growing children and adolescents less than 18 years old who required an epiphysiodesis with leg-length discrepancy (LLD) of 2 cm to 6 cm with minimum two years of follow-up was conducted. Characteristics including age at surgery, gender, epiphysiodesis location, side, operative time, LOS and hardware removal were compared across treatment groups. LLD, expected growth remaining (EGR) and bone age were determined preoperatively and at most-recent visit. The correction ratio (change in EGR) was calculated along with a 95% confidence interval (CI) to assess if correction in leg length was achieved. Results: A total of 115 patients underwent epiphysiodesis in the femur (53%), tibia (24%) or a combination (24%). The cohort was 47% male, with a mean age of 12.6 years (7.7 to 17.7) at surgery. Median follow-up was 3.7 years (2.0 to 12.7). In all, 23 patients underwent PETS and 92 patients had PDED. Both treatment groups achieved expected LLD correction. There was no significant difference in median operative time, complication rates or LOS. PETS patients returned to activity at a mean 1.4 months (interquartile range (IQR) 0.7 to 2.1) while PDED patients returned at a mean 2.4 months (IQR 1.7 to 3) (p < 0.001). Conclusion: Effectiveness in achieving expected correction, LOS and operative time are similar between screw and drill/curettage epiphysiodesis. Patients undergoing PETS demonstrated a faster return to baseline activity than patients with PDED. Level of Evidence: III